(3YbO GdJCLjQ GdJehjdj (B:s "(3OQGSI ebGQfI(B" /s - (3eGgQ, hdjO Ydjs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3YbO GdJCLjQ GdJehjdj OQGSI ebGQfI jOhQ gPG GdHMK HTcd YGe Mhd YbO GdJCLjQ GdJehjdj hYdi hLg GdNUhU HjGf eagheg aj GdJTQjYGJ GdebGQfI, heOi TQYJg aj Gdabg GdESdGej, heYQaI JfXjeg ef GdfGMjI GdOhdjI HGdEVGaI Edi HjGf NUGFUg hJejjRg Yf eG jNJdW Hg ef YbhO, hjdj Pdc YQV GdfXGe GdbGfhfj dYbO GdJCLjQ GdJehjdj ef NdGd BKGQ GdYbO GdeJeKdI aj GdJRGeGJ GdeDLQ hGdeSJCLQ hYdGbJge HGdehQO hcjajI GfbVGA YbO GdJCLjQ GdJehjdj HGfJgGA eOJg Ch dCSHGH YGQVI(B.s
(3GdeMJhjGJ (B: (3ebOeI(B-(3GdaUd GdChd (B: (3GdJcjja GdbGfhfj dYbO GdJCLjQ GdJehjdj, hjTed GdeHMK GdChd (B: (3eaghe hUhQ YbO GdJCLjQ GdJehjdj (B... (3GdaUd GdKGfj (B: (3GdSeGJ GdPGJjI GdeJaQOI dYbO GdJCLjQ GdJehjdj, hjTed GdeHMK GdChd (B: (3CWQGa YbO GdJCLjQ GdJehjdj heOi LhGR GdJfGRd Yfg (B... (3GdaUd GdKGdK (B: (3eOi JCcjO CKGQ YbO GdJCLjQ GdJehjdj Ydi CgejJg GdJLGQjI, hjTed GdeHMK GdChd (B: (3JCcjO GdJRGeGJ GdeDLQ Ydi GdCgejI GdJLGQjI dYbO GdJCLjQ GdJehjdj (B... (3Ke JCJj aj GdfgGjI GdNGJeI(B-(3bGFeI GdeQGLY(B.s
(3HHdjhLQGajI (B: (3UaMI (B179-186.s
Keywords: (3GdJCLjQ GdJehjdjs -- (3bhGfjf hJTQjYGJs; (3YbhO GdEjLGQs -- (3bhGfjf hJTQjYGJs; (3GdEjLGQGJs -- (3bhGfjf hJTQjYGJs; (3GdedcjIs -- (3bhGfjf hJTQjYGJs; (3GdeGdc hGdeSJCLQs -- (3bhGfjf hJTQjYGJs; (3GdYbhO GdeSeGIs; (3CQcGf GdYbOs